Analisis Potensi Pemanfaatan Energi Angin pada Kawasan Wisata Bukit Gua Jepang Kota Lhokseumawe - Panji Aji Riha Wijayanto; Muhammad Daud; Adi Setiawan; Arnawan Hasibuan (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
In order to maintain energy security and independence due to the decline in fossil energy production, especially oil and gas, as well as the world's commitment to minimize greenhouse gas emissions, the Indonesian government continues to optimize the use of new and renewable energy. Aceh has a new renewable energy potential of 16,882 MW with a wind energy potential of 894 MW. This study aims to analyze the potential of wind energy in the tourist area of Bukit Goa Japan in Lhokseumawe, Aceh, to be used as a source of lighting energy in the area. Wind speed measurements were carried out at 08:30 AM to 08:00 PM. Time interval of data collection every half hour at a height of three meters and five meters from the ground directly and by installing a wind turbine with a maximum power capacity of 400 W. The results showed that the Bukit Goa tourist area in Japan has an average daily wind speed of 0. 7 m/s which has the potential to produce an average electric power of 8.9 W when using a three-blade wind turbine at a height of three meters from the ground, with peak power obtained at 11:30 AM which is 13.33 watts. Meanwhile, wind turbines that use five blades do not produce any power at all. Meanwhile, at a height of five meters the daily average wind speed is 0.63 m/s which has the potential to generate a power of 9.98 W with the peak power obtained at 01:00 PM which is 14.85 W.